Striatal bases of temporal discounting in early adolescents. (July 2020) - Hamilton, Kristen R.; Smith, Jason F.; Gonçalves, Stefanie F.; Nketia, Jazlyn A.; Tasheuras, Olivia N.; Yoon, Mark; Rubia, Katya; Chirles, Theresa J.; Lejuez, Carl W.; Shackman, Alexander J.
Abstract: Steeper rates of temporal discounting—the degree to which smaller-sooner (SS) rewards are preferred over larger-later (LL) ones—have been associated with impulsive and ill-advised behaviors in adolescence. Yet, the underlying neural systems remain poorly understood. Here we used a well-established temporal discounting paradigm and functional MRI (fMRI) to examine engagement of the striatum—including the caudate, putamen, and ventral striatum (VS)—in early adolescence (13–15 years; N = 27). Analyses provided evidence of enhanced activity in the caudate and VS during impulsive choice. Exploratory analyses revealed that trait impulsivity was associated with heightened putamen activity during impulsive choices. A more nuanced pattern was evident in the cortex, with the dorsolateral prefrontal cortex mirroring the putamen and posterior parietal cortex showing the reverse association. Taken together, these observations provide an important first glimpse at the distributed neural systems underlying economic choice and trait-like individual differences in impulsivity in the early years of adolescence, setting the stage for prospective-longitudinal and intervention research. Highlights: Striatal activation was greater in early adolescents during smaller-sooner (SS) choices. Activation was greater during SS than larger-later (LL) choices in caudate and ventral striatum. Trait impulsivity was associated with greater putamen activation during SS trials. Trait impulsivity was associated with greater middle frontal gyrus activation during SS choices. Trait impulsivity was associated with greater activation during LL choices in supramarginal gyrus.